2009
DOI: 10.1016/j.biopsycho.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress on heart rate complexity—A comparison between short-term and chronic stress

Abstract: This study examined chronic and short-term stress effects on heart rate variability (HRV), comparing time, frequency and phase domain (complexity) measures in 50 healthy adults. The hassles frequency subscale of the combined hassles and uplifts scale (CHUS) was used to measure chronic stress. Shortterm stressor reactivity was assessed with a speech task. HRV measures were determined via surface electrocardiogram (ECG). Because respiration rate decreased during the speech task (p < .001), this study assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(203 citation statements)
references
References 70 publications
12
185
2
4
Order By: Relevance
“…Research mainly focused on understanding the changes in HRV related to long-term stressors on autonomic nervous system activity. Schubert et al (2009) reported that certain non-linear HRV parameters were useful to detect chronic stress while others found that chronically stressed individuals show decreased HR (Furlan et al, 2000;Lucini et al, 2005).…”
Section: Further Opportunities In Hr and Hrv In Dairy Cattle Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Research mainly focused on understanding the changes in HRV related to long-term stressors on autonomic nervous system activity. Schubert et al (2009) reported that certain non-linear HRV parameters were useful to detect chronic stress while others found that chronically stressed individuals show decreased HR (Furlan et al, 2000;Lucini et al, 2005).…”
Section: Further Opportunities In Hr and Hrv In Dairy Cattle Researchmentioning
confidence: 99%
“…Research mainly focused on understanding the changes in HRV related to long-term stressors on autonomic nervous system activity. Schubert et al (2009) reported that certain non-linear HRV parameters were useful to detect chronic stress while others found that chronically stressed individuals show decreased HR (Furlan et al, 2000;Lucini et al, 2005).The study of Mohr et al (2002) involving dairy calves suffering from BVD showed that RQA parameters in describing the response to a pathological load.The application of the above mentioned non-linear parameters is promising, however, further research is required to better understand the welfare impact of chronic stress Kovács, Jurkovich, Bakony, Szenci, Póti and Tőzsér 326 and disease-indicated loads by finding clearer relations with non-linear HRV.On the base of associations of suppressed immune state and chronic stress, another way to interpret long-term effects of challenged situations is the study of HRV together with, for example, somatic cell count (SCC) investigation and immunological tests, hereby chronic stress may be more extensively studied. Consequently, a more integrated view of stress reactions in farm animals is needed for the expansion of approaches how chronic stress can be conceptualised in research on HRV.…”
mentioning
confidence: 99%
“…Means (± standard deviation) of heart rate variability and urinary catecholamine levels described 17,18) . As well, exposure to high levels of stress in the workplace increases the log LF power [ln(ms 2 /Hz)] 9) .…”
Section: Discussionmentioning
confidence: 99%
“…Further the formant frequency analysis has been carried out with a DSP Tool (PRAAT) to obtain the various formant frequencies [2] and F1, F2 and F3 formant frequency vs utterances duration response is plotted to observe the RR-cycle in the state of anger and fear [4,[10][11][12][13][14][15] .…”
Section: Methodsmentioning
confidence: 99%